Sodium‐glucose co‐transporter inhibitors, their role in type 1 diabetes treatment and a risk mitigation strategy for preventing diabetic ketoacidosis: The STOP DKA Protocol. Issue 10 (30th June 2019) - Goldenberg, Ronald M.; Gilbert, Jeremy D.; Hramiak, Irene M.; Woo, Vincent C.; Zinman, Bernard
Abstract: Recent phase 3 clinical trials have evaluated the impact of adding sodium‐glucose co‐transporter (SGLT) inhibitors to the type 1 diabetes armamentarium. These trials studied SGLT2 inhibitors (dapagliflozin and empagliflozin) and a dual SGLT1 and SGLT2 inhibitor (sotagliflozin), and demonstrated that these oral non‐insulin antihyperglycaemic medications are able not only to improve glycaemic control, but also to reduce body weight and extend time in range without increasing rates of hypoglycaemia in type 1 diabetes. Diabetic ketoacidosis (DKA) is a feature of type 1 diabetes and the risk is increased when SGLT inhibitors are used in type 1 diabetes. To minimize the risk of DKA and still gain the multiple benefits, we developed the "STOP DKA Protocol ", an easily accessible and practical tool, that provides a risk mitigation strategy for reducing DKA in patients with type 1 diabetes being treated with SGLT inhibitors.